The Effect of Lips Reading on Language Ability on Mentally Retarded Children in Special School - Ni Ketut Mendri; Atik Badi’ah; Bondan Palestin; Heru Santoso Wahito Nugroho; Muhammad Najib (Health Notions, 2022)
Background: Mentally retarded children have a disorder at a level of intelligence below the average normal child. RM children have difficulty in arranging the form and structure of sentences. Children with RM need to get speech therapy to improve language disorders so that they become productive and improve language skills. The importance of applying lips reading can stimulate language skills so that they can arrange words and string words in sentences. Based on a preliminary study in June 2019 of five (SLB) in Yogyakarta SLBN Pembina, SLBN 1 Bantul, SLBN Sewon Bantul, SLBN Sleman and SLB Rela Bhakti I Gamping. Observations during learning in special schools found that (100%) of five special schools used sign language, they had not been trained using the Lips Reading method. Objectives: To know the influence of lips reading on the language ability of mentally retarded children in special schools. Methods: The type of research was quasi-experimental with pre-test post-test with control group design. The sample was taken by purposive sampling. Data were analyzed using t-test, Wilcoxon and Mann Whitney. Results: The language ability of RM children in Special Schools of Yogyakarta between the experimental and control groups with p value <0.05. Conclusion: There is an influence of Lips Reading on the Language Ability of Mentally Retarded Children in Special Schools Keywords: lips reading; language ability; mentally retarded children; fruit-vegetable-flower picture